Status and Constraints of Jute Cultivation in Bangladesh: An Experience from Selected Upazilas under Chandpur District - Islam , Mohammad Muzahidul; Xiaoying, Jian; Uddin, Md Ektear; Bhuiyan, Faruk (Asian Journal of Agriculture and Rural Development, 2015)
This study aimed at exploring the obstacles of jute cultivation under Chandpur Districts in Bangladesh by the principle component analysis (PCA). The required data were collected through structured interview schedule from 803 jute farmers sampled conveniently. Though jute diversified industry has been seen as potential since the last decade in Bangladesh, raw jute production is not satisfactory due to several obstacles. The study has identified three categories of constraints that hinder sustainable jute production. These are lack of capital and inputs, knowledge and natural resources, and market information. Basically farmers cultivate jute for earning profit but they are not conscious about forward market. Lack of jute diversification knowledge is the unique findings of this study. The findings may help policy makers and stakeholders for taking effective decision in addressing the barriers to jute cultivation in Bangladesh.